Crecimiento de los rebrotes de Pistacia lentiscus y Quercus coccifera después de un incendio - Abril M.; Gracia C.A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The growth of resprouting individuals of two typical Mediterranean species, Pistacia Lentiscus and Quercus coccifera, was studied over an annual cycle, during the second year after burning. Growth was estimated in two ways: direct estimation of the increase in stem diameter in the field, and cytological estimation based on the increase in number of xylem cells. In general, in both species growth takes place in spring and in the autumn, when temperatures and available water is favourable for the physiological activity of the plants. Both species show a resting state in winter, which is caused by low temperatures. In summer, when high temperatures favour physiological activity, the water deficit is limiting and in most plants creates a latent state in the cambium, with a cessation of growth. Differences between resprouting individuals were observed within the same species, as well as between species.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)